Meri cycle - Danish, Ahmed Auranzeb; Naqi, Mustafaye Rumana, Husain (book group Karachi, 2004)
"Meri Cycle" is a popular Urdu children's book that tells the story of a young child who receives a new bicycle as a gift. The book follows the child's excitement and joy as they learn to ride the bike, explore their neighborhood, and make new friends.